Calibration coefficients for high-purity germanium-based monitoring of uranium and thorium in lungs - C. S. Charubala; S.L. Asanali; V. Santhanakrishnan; G. Ganesh; M. S. Kulkarni (Radiation Protection and Environment)
HPGe based detection systems are used for in-vivo monitoring of radiation workers to detect internal contamination due to low energy photon emitters such as actinides. HPGe Detector Array (HDA) commissioned in a steel room and calibrated using Lawrence Livermore National Laboratory (LLNL) realistic torso phantom has been used for the routine internal monitoring purposes in our laboratory. Present work deals with the calibration of HDA system for uranium and thorium detection in lungs. Physical measurements were performed using LLNL physical phantom with indigenously developed uranium capsule embedded lungs set. In addition, Monte Carlo simulations were carried out using FLUKA code and International Commission on Radiation Protection (ICRP) Adult Male (AM) voxel phantom to estimate the calibration coefficients for interested energies of uranium and thorium. Calibration coefficients from the experiment and simulations suggest a great similarity between values obtained from uranium embedded physical lungs set and ICRP-AM thorax phantom for 63keV and 93keV emissions. However, significant deviation was observed in calibration coefficient for 186keV. This study also leads to numerical calibration of HDA system for thorium detection. HDA system was calibrated for uranium and thorium detection in lungs. Physical and numerical calibration results were compared to understand the deviations.